Effect of Attenuated Salmonella enterica Serovar Typhimurium Expressing a Streptococcus mutans Antigen on Secondary Responses to the Cloned Protein - Jespersgaard, Christina (American Society for Microbiology, 2001)
Attenuated Salmonella enterica serovar Typhimurium has been used for targeted delivery of recombinant antigens to gut- and nose-associated lymphoid tissues. Contradictory reports have described the effect of preexisting immunity to the antigen delivery vehicle. We decided to examine this discrepancy by studying the effect of immunizing mice by the intranasal (i.n.) route with Salmonella expressing an insoluble protein and to study the ability to augment recall responses by boosting with either Salmonella-expressed protein or purified soluble protein alone. The glucan-binding domain (GLU) of the enzyme glucosyltransferase (GTF), which is an important virulence factor of Streptococcus mutans, was recombinantly expressed in the insoluble phase in S. enterica serovar Typhimurium, and the immunogenicity of this construct was studied in mice. We examined the induction of primary immune responses by insoluble GLU polypeptide delivered in Salmonella at week 1 (groups 1 and 2) and recall responses after a week 15 boost with either Salmonella expressing GLU (group 1) or purified GLU polypeptide (groups 2 and 3). Group 4 served as the control and received phosphate-buffered saline alone by the i.n. route. Significant anti-GLU serum immunoglobulin G (IgG) levels were seen in groups 1, 2, and 3 at week 18 (P < 0.001), i.e., 3 weeks after the booster immunization. Mice in group 2, who received Salmonella followed by GLU, had the highest GLU-specific IgG levels among all groups. The serum IgG levels persisted in all responding groups for at least 7 weeks after the boost (week 22). The IgG2a/IgG1 subclass ratio of serum anti-GLU antibodies in group 1 significantly increased after the boost. These results support the induction of a type 1-like immune response to GLU after primary and booster immunizations with Salmonella expressing GLU. On the other hand, group 2 mice, which received Salmonella expressing GLU as the primary dose and soluble protein as the booster dose, exhibited a shift from a type 1-like to a more type 2-like immune response to GLU following the boost. These results indicate that S. enterica serovar Typhimurium is an excellent delivery vehicle for the insoluble and recombinantly expressed GLU of GTF and that this construct was especially effective in priming the host for a secondary response to soluble GLU polypeptide.